PPARγ induces the paroxysm of endometriosis by regulating the transcription of MAT2A gene - Zhang, Shun (Am J Transl Res, 2021)
Objective: To investigate the molecular mechanism of PPARγ impacting the paroxysm of endometriosis. Methods: Immunohistochemistry, qRT-PCR and Western Blot were used to determine the expression level of PPARγ and MAT2A in Eu, Ec and normal endometrial tissue (control). ESC and NSC were separately isolated. PPARγ was silenced in NSC and was up-regulated in ESC. Rosiglitazone (RSG) were used to incubate with ESC. Proliferation, apoptosis, invasion, and ultrastructure of cells were evaluated in vitro. The combination between PPARγ and the promoters of MAT2A was detected by dual-luciferase reporter assay. Results: MAT2A was up-regulated and PPARγ was down-regulated in Eu and Ec. The cell viability and the ability of migration and invasion declined greatly after up-regulating the expression of PPARγ or treating with RSG in ESC. Meanwhile, the expression level of MAT2A was significantly inhibited. Plenty of vacuoles and classical morphological changes of apoptotic cells were observed in the ESC with PPARγ over-expressed. The cell viability and the ability of migration and invasion of NSC with PPARγ silenced were promoted greatly. Meanwhile, the expression level of MAT2A was significantly up-regulated. Conclusion: The paroxysm and development of endometriosis were impacted by over-expressing PPARγ or introducing of RSG by inhibiting the transcription of MAT2A.